PENGGUNAAN BAHASA INDONESIA RAGAM LISAN PARA DHAMMADUTA (STUDI KASUS DI KABUPATEN SEMARANG) - Santi Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
This study aims to find out the variety of spoken languages used by the dhammaduta, thefunctions of various spoken languages used by the dhammaduta, and the understanding of thespoken language of the dhammaduta by Buddhists. This study uses qualitative research methods,with a case studies approach. The results of the study show that in various Dhamma sermonsfound a variety of standard and non-standard languages. The variety of languages is not the onethat dominates. The characteristic that can be found in it is the symptom of interference with theJavanese sentence pattern, there are symptoms of code switching and mixed code both in Paliand Javanese. Linguistic functions, forms of discourse whose nature is to inform, explain,strengthen, remind and so on. Language functions in dhamma sermons fulfill personal functions,fatigue functions, directive functions, referential functions, metalingual functions ormetalingualistic functions and imaginative functions. Factors that make listeners find it easierto understand are (1) The language of dhammadesana tends to be simple and straightforward,(2) Simple and actual dhamma-material material, (3) The way in which dhammaduta is deliveredand performed.